A comprehensive evaluation of a diabetes quality improvement project in privately owned primary care practices that serve minority patients - Hoof, Thomas J Van; Meehan, Thomas P; Kelveyalbert, Michele; Galusha, Deron; Curry, Maureen; Barr, Judith K (American Journal of Medical Quality, 2012)
The authors conducted a diabetes quality improvement project in 5 privately owned primary care practices serving at least 25% minority patients. Interventions included group-specific and practice-specific training on an electronic patient registry, cultural competency practices and tools, and selected quality improvement strategies. The authors conducted a comprehensive evaluation involving quantitative and qualitative data to assess project impact. Although overall clinical performance did not improve over the 14- to 20-month project time frame, other practice structural characteristics and processes did show improvement: successful implementation of the registry and clinician reminders in all practices, institution of team care and patient reminders in 4 practices, and collection of patient race/ethnicity data in 4 practices. These results highlight the difficulty of bringing about clinical improvement in this subset of practices and also the importance of conducting comprehensive evaluations to fully understand and interpret multicomponent quality improvement projects. © 2012 by the American College of Medical Quality.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/094-542-892-323-004 tex.type: [object Object]
Keywords: Aged; Diabetes Mellitus; Humans; Minority Groups; Primary Health Care; Private Practice; Program Evaluation; Quality Assurance; Health Care; Quality Improvement; aged; article; dept.pch; diabetes; diabetes mellitus; evaluation; health care quality; human; methodology; minority group; minority patients; organization and management; primary care; primary health care; private practice; quality improvement; standard; total quality management

An Examination of Exposure to Traumatic Events and Symptoms and Strengths for Children Served in a Behavioral Health System of Care. - Whitson, Melissa L; Connell, Christian M; Bernard, Stanley; Kaufman, Joy S (Journal of Emotional and Behavioral Disorders, 2012)
The present study examined how exposure to traumatic events impacts children with severe emotional disturbance who are being served in a school-based system of care. Multilevel growth curve models were used to examine the relationships between a child's history of traumatic events (physical abuse, sexual abuse, or domestic violence) and behavioral and emotional strengths, internalizing problem behaviors, or externalizing problem behaviors over 18 months. Results indicate that children receiving services (N = 134) exhibited increased emotional and behavioral strengths and decreased internalizing and externalizing problem behaviors from enrollment to 18 months follow-up. Children with a history of traumatic events improved more slowly than children without such a history on both strengths and internalizing problem behaviors, even after controlling for dosage of services received and other characteristics previously found to predict outcomes. Gender was also related to improvement in internalizing symptoms. Results highlight the continued need to assess the impact of exposure to traumatic events for children served in a system of care.
10 citations (Crossref) [2023-10-31] Place: United States Whitson, Melissa L. Yale University, New Haven, CT, USA. Connell, Christian M. Yale University, New Haven, CT, USA. Bernard, Stanley. Southern Connecticut State University, New Haven, CT, USA. Kaufman, Joy S. Yale University, New Haven, CT, USA.
Keywords: children's mental health; dept.pch; emotional and behavioral problems and strengths; multilevel models; peer-reviewed; systems of care; trauma